Regulation of Big Tech in the EU - Iwona Windekilde; Anders Henten (International Telecommunications Society (ITS), 2023)
During the past few years, there has been a steeply increasing political interest in regulating Big Tech companies and digital platforms in general. For many years, from the establishment of the first Internet-based IT companies and onwards, the dominant political view has been that policymaking should, to a large extent, stay away from regulating or only lightly regulate the Internet-based industries. The risk of doing more harm than good would be too high - not having sufficient knowledge on how these industries would develop and risking constraining the innovativeness of the Internet-based industries. This has clearly changed today. In Europe as well as the US and elsewhere around the world, policy initiatives are taken to regulate Big Tech and the Internet-based industries in general. This applies to the protection of individuals/users/consumers as well as regulating competition. The reason is that a consensus has been gaining ground that we now have sufficient experience not only with the benefits to the economy, to users, and society as such of the developments of Internet and Internet-based industries but also with the downsides in terms of harm to individuals/users/consumers and social and political relations and institutions and to small and upcoming innovative companies. This has led to an increasing surge in rules and regulations for the protection of individuals as well as the competitive conditions on markets. The aim of this paper is to provide an overview of the ongoing and upcoming trends in Big Tech regulation with a focus on EU. Emphasis is on the Digital Markets Act (DMA) and the Digital Services Act (DSA) though it is well understood that there are other kinds of regulation that also affect digital platforms including Big Tech companies. (...)
Keywords: 330